Reinvigorating the Function of Mushola, Langgar, and Padepokan in Conventional Education: Cultural and Historical Analyses in Indonesia - Yusgiantara, Akbar; Jailani, Tutus Gilang (YASIN, 2025)
This article examines the structures and roles of Islamic education in prayer rooms (mushola), tiny mosques (langgar), and hermitages (padepokan) within the framework of digital change and the educational challenges of the 21st century. This research employs a qualitative approach via a literature review, demonstrating that non-formal institutions have a key role in character development, spiritual growth, and the dissemination of Islamic values in society. Mushola functions as a hub for fundamental religious education and practical worship training; langgar highlights community-oriented Quranic instruction and Islamic studies; whilst padepokan concentrates on profound spiritual growth via Sufism and ethical enhancement. The research indicates that rejuvenating these institutions necessitates the amalgamation of conventional pedagogy with digital innovation to maintain relevance for the younger generation. Consequently, cooperation among government, community, and educational institutions is vital to maintain these entities as adaptable and contextual pillars of Islamic education.